The Evolution of Juvenile Schönlein-Henoch Purpura - O.E. Chernyshova; V.V. Gerasymenko; E.D. Yegudina; O.V. Syniachenko; M.V. Ermolaeva (Zaslavsky O.Yu., 2016)
Background. Hemorrhagic vasculitis, or Schönlein-Henoch purpura (SHP), is the most common type of systemic vasculitis in childhood, and peculiarities of the further evolution of the pathological process in adult patients remain unexplored. Objective: to study the evolution of juvenile SHP, comparing the nature of lesions of the skin, joints, heart and kidneys in patients in childhood and adulthood. Material and methods. The study included 92 patients (61 men and 31 women with the average age of 27 years, and the average age of disease onset - 11 years). I degree of the activity of the pathological process is determined in 40 % of cases, II - in 35 %, III - in 25 %. Seropositivity by hyperimmunoglobulinemia A occurred in 27 % of cases, by the presence of rheumatoid factor - in 21 %. At the time of the survey, cutaneous syndrome was diagnosed in 55 % of patients, joint one - in 45 %, kidney one - in 71 %. Renal biopsy was performed in 15 cases. Results. The cutaneous, cutaneous-joint-abdominal and cutaneous-abdominal-renal forms of the disease, lesions of the skin, gastrointestinal tract, wrist, ankle and knee joints become rarer in the process of juvenile SHP evolution, but exceptionally renal variant of the pathological process, changes of skeletal muscles, liver, spleen and the heart are revealed more often, chronic kidney disease with the renal failure progression is developed in 12 % of patients (in 17 % of cases of nephropathy), sacroiliitis, spondylopathy, tendovaginitis, enthesopathies, epiphyseal osteoporosis and meniscitis of the knee joints are arisen, II, III, VI and IV morphological classes of Henoch glomerulonephritis are formed in a ratio of 8 : 4 : 2 : 1 with tubulointerstitial component in all cases, and lymphohistiocytic infiltration of the vascular wall is the unfavorable sign for the prognosis of the disease. Conclusions. In cases of transition of juvenile SHP into the chronic adult form, the disease often obtain progressive course that, first of all, refers to the pathology of the joints and kidneys.